2018
DOI: 10.3892/ijmm.2018.3753
|View full text |Cite
|
Sign up to set email alerts
|

TGM2 knockdown reverses cisplatin chemoresistance in osteosarcoma

Abstract: In the past decades, chemotherapy has resulted in improved outcomes for patients with osteosarcoma. However, resistance to chemotherapy often leads to poor prognoses. Cisplatin is a standard drug for osteosarcoma therapy, and chemoresistance to cisplatin in osteosarcoma limits the effectiveness of chemotherapy drugs. Transglutaminase 2 (TGM2) is a member of the transglutaminase family, and it is reported to be associated with chemoresistance in various types of cancer. The present study aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…Regarding the multifactorial resistance profile, the present study aimed to investigate other potential signaling pathways involved in cisplatin sensitivity induced by MET in addition to mTOR signaling. In both sensitive and resistant cells, MET altered transcriptional processes, regulated apoptosis, oxidation-reduction processes and proteins associated with leukocyte degranulation, with 99 common significantly altered targets, of which some have been previously described: AK3 ( 68 ), ALDH1A1 ( 69 ), ANXA2 and 4 ( 70 , 71 ), CFL1 ( 72 ), CRYAB ( 73 ), filamin A (FLNA) ( 74 ), GSTP1 ( 75 ), HMGA1 and G6PD ( 76 ), hnRNPA2B1 ( 77 ), HSP90 ( 78 ), IGF2BP1 ( 79 ), integrin b1 (ITGB1) ( 80 ), MYH9 ( 81 ), PKM2 ( 82 - 84 ), STIP1 ( 85 ), TGM2 ( 86 ), TKT ( 87 ) and TRAP1 ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the multifactorial resistance profile, the present study aimed to investigate other potential signaling pathways involved in cisplatin sensitivity induced by MET in addition to mTOR signaling. In both sensitive and resistant cells, MET altered transcriptional processes, regulated apoptosis, oxidation-reduction processes and proteins associated with leukocyte degranulation, with 99 common significantly altered targets, of which some have been previously described: AK3 ( 68 ), ALDH1A1 ( 69 ), ANXA2 and 4 ( 70 , 71 ), CFL1 ( 72 ), CRYAB ( 73 ), filamin A (FLNA) ( 74 ), GSTP1 ( 75 ), HMGA1 and G6PD ( 76 ), hnRNPA2B1 ( 77 ), HSP90 ( 78 ), IGF2BP1 ( 79 ), integrin b1 (ITGB1) ( 80 ), MYH9 ( 81 ), PKM2 ( 82 - 84 ), STIP1 ( 85 ), TGM2 ( 86 ), TKT ( 87 ) and TRAP1 ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGM2, a cross-linking enzyme, has been demonstrated to be tightly associated with chemosensitivity in diverse cancers [ 38 , 39 ]. Moreover, previous study revealed that TGM2 expression was enhanced in cisplatin-resistant OS cells and its deficiency elevated the chemosensitivity of osteosarcoma to cisplatin [ 23 ]. Therefore, we wondered whether TGM2 participated in MTX resistance of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous report revealed that TGM2 promoted the progression of osteosarcoma [ 22 ]. Moreover, TGM2 was also reported to be related to chemoresistance in multiple cancers [ 23 , 24 ]. Nevertheless, there is no evidence that TGM2 plays a role and the relationship between TGM2 and miR-494-3p in MTX sensitivity of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Suppressing TGM2 expression can promote meningioma cell death by reducing AKT phosphorylation and caspase-3 ( 34 ), while AKT activation may drive normal breast mammary epithelial MCF10A cells into EMT via TG2 signaling ( 35 ). Moreover, TGM2 silencing can suppress AKT activation in the Saos2-cIS-R cells ( 36 ). All these data suggest that the reduced expression of TG2(TGM2)/AKT may promote the drug sensitivity of cancer cells via EMT reversal.…”
Section: Discussionmentioning
confidence: 99%